Toksisitas Subletal Limbah Cair Batik Hasil Biosorpsi Terhadap Struktur Histologis Ginjal Ikan Mas (Cyprinus carpio) - Khalil Ibrahim Sani; Sri Lestari; Atang Atang (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2020)
Histopathological studies related to the kidney of fish exposed to batik wastewater resulted from the biosorption process are necessary because the kidney is an target organ that plays an important role in maintaining water balance and osmoregulation. This research aims to determine the effect of batik wastewater resulted from the biosorption process exposure on kidney histology of Carp (Cyprinus carpio) and determine the concentration that has the most effect on it. The treatment consists of K0 (control) and three treatments of batik wastewater resulted from the biosorption process with different concentration from 25 %, 50 %, and 75 % LC50 96h, ie K1 1,32; K2 2,64, and K3 3,96 % v.v-1. The carp were exposed to batik wastewater resulted from the biosorption process for 7 days, and on the 8th day the fish was dissected, and the kidney was taken for histology process. The result of the research shows that exposure to batik wastewater resulted from the biosorption process with different concentrations give negative impact on the carp kidney such as tubular hypertrophy, tubular necrosis, and glomerular necrosis.